A CROSS-SECTIONAL STUDY OF ANTIHYPERTENSIVE DRUG UTILIZATION PATTERN IN RURAL POPULATION OF SOUTHERN INDIA - DHANIYALA, KISHAN; CHANDRA, VURIMI BHOPAL; RAYAM, SRIHARSHA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objective of the study is to study the antihypertensive drug utilization pattern, demographic profile, and associated comorbid conditions of hypertensive patients in the rural population of Southern India. Methods: This study was a cross-sectional, community-based, door-to-door survey of hypertensive patients. The details of the patients which include age, sex, body mass index (BMI), past medical history, usage of drugs for hypertension (HTN), any other related drugs, and comorbid conditions were collected in this study. Results: As per the results, the mean age of study participants was 54.68 years, men were 62.31% women were 37.68%, mean BMI was 30.48 kg/m2. In associated comorbidities with HTN, Diabetes was the most common with 19.4%. As per usage of antihypertensive drugs, In Monotherapy, angiotensin-converting enzyme (ACE) inhibitors/angiotensin receptor blockers (ARBs) occupy 16.4% followed by beta-blockers (BB) 13.4%.In 2+ drug therapy, Diuretics were 26.8% followed by BB 22.7% and in drug combinations, the combination of ACE/ARB + Diuretics were 11.5% followed by ACE/ARB + calcium channel blocker at 8.2%. Conclusion: HTN was more common in Men and the BMI was also on the higher side in hypertensive patients. In associated comorbidities with HTN, Diabetes was the most common disease. Antihypertensive drugs usage pattern shows that in monotherapy, ACE inhibitors/ARBs were the most commonly used drugs. In 2+ therapy, the most common add-on drugs were diuretics. In combination therapy, the most common combination was ACE/ARB + Diuretics.